2013
DOI: 10.1002/2013jd020445
|View full text |Cite
|
Sign up to set email alerts
|

Solar irradiance reduction via climate engineering: Impact of different techniques on the energy balance and the hydrological cycle

Abstract: [1] Different techniques of solar radiation management (SRM) have been suggested to counteract global warming, among them the injection of sulfur into the stratosphere, mirrors in space, and marine cloud brightening through artificial emissions of sea salt. This study focuses on to what extent climate impacts of these three methods would be different. We present results from simulations with an Earth system model where the forcing from the increase of greenhouse gases in a transient scenario (RCP4.5) was balan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
196
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 157 publications
(216 citation statements)
references
References 68 publications
(77 reference statements)
8
196
2
Order By: Relevance
“…First, MAECHAM5-HAM-SALSA was used to define the stratospheric aerosol fields and optical properties in several volcanic eruption and SRM scenarios. Following the approach introduced in Timmreck et al (2010) and Niemeier et al (2013), these parameters were then applied in the Max Planck Institute Earth System Model (MPI-ESM) in order to study their effects on the temperature and precipitation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, MAECHAM5-HAM-SALSA was used to define the stratospheric aerosol fields and optical properties in several volcanic eruption and SRM scenarios. Following the approach introduced in Timmreck et al (2010) and Niemeier et al (2013), these parameters were then applied in the Max Planck Institute Earth System Model (MPI-ESM) in order to study their effects on the temperature and precipitation.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies (Bala et al, 2008;Kravitz et al, 2013a, b;Niemeier et al, 2013) have already shown that geoengineering leads to a reduction in the global precipitation compared to the climate without geoengineering. In our SRM simulation, we obtain a precipitation reduction of 0.11 mm day −1 (2.8 %), which is clearly larger than the impact after the volcanic eruption.…”
Section: Climate Effects From Concurrent Volcanic Eruption and Srm -Rmentioning
confidence: 99%
“…Aswathy et al (2015) and Niemeier et al (2013) compared stratospheric sulfur aerosol injections to the brightening of marine clouds in terms of the hydrological cycle and extremes in temperatures and precipitation. Crook et al (2015) compared the three methods used in this study, but restricted the study to temperatures and precipitation.…”
Section: Introductionmentioning
confidence: 99%
“…1a). This injection strategy corresponds to the injection scenarios in most previous studies, although they have used different widths for the injection area (Heckendorn et al, 2009;Jones et al, 2016;Niemeier et al, 2011;Pierce et al, 2010;Pope et al, 2012;Tilmes et al, 2015). In the Northern Hemisphere (NH) scenario, sulfur was injected only in the Northern Hemisphere between latitudes 10 and 30 • N (Fig.…”
Section: Fixed Injection Areasmentioning
confidence: 99%